UJI AKTIVITAS ANTIBIOSIS PSEUDOMONADS PENDARFLUOR TERHADAP Rigidoporus lignosus (Klotszch) Imazeki PENYEBAB PENYAKIT AKAR PUTIH - . Hasanuddin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
The potential of fluorescent bacteria as biological control agents for white root disease caused by Rigidoporus lignosus has been investigated. Isolation of bacteria from the soil using S1 media produced two fluorescent bacteria isolates. Using the Microbact 12A+12B method, both bacteria were identified as Pseudomonas fluorescens and P. aeruginosa. These two species of bacteria were then used as antibiosis activity test against R. lignosus. Four series antibiosis activity tests were done, that were antibiosis test of media culture bacteria growth to R. lignosus colony, antibiosis test of dry fluorescent pigment extract to R. lignosus, influence of Fe3+ to antibiosis activity of bacteria test, and affinity of media supernatant to Fe3+. The results were: antibiosis activity of King’s B (KB) media was more effective than media 523 in the inhibition of R. lignosus colony growth. There was no significant different antibiosis activity of dry fluorescent pigment extract from media KB and media 523 in the inhibition of R. lignosus colony growth. The level of Fe3+ in the media might influence antibiosis activity of fluorescent pigment. Affinity test of KB supernatant from fluorescent bacteria culture with Fe3+ showed an absorption peak of 410 nm on spectrophotometer, and none for the fungi. These results indicate that P. fluorescens and P. aeruginosa produce cathecol-type siderophore with high affinity against Fe3+ compared with hydroxamate-type siderophore which is generally produced by fungus.